Front Cover: Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography (Adv. Quantum Technol. 6/2021). Issue 6 (8th June 2021) - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; von Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al.
Abstract : The cover image presents an electrically controllable quantum‐dot‐molecule (QDM) device which can act as spin–photon interface in quantum communication networks. Electrical contacts enable efficient control of the conversion between stationary qubits and flying qubits, represented by the spin degree of charge carriers in the QDM and emitted photons, respectively. The spin–photon interface includes a monolithically integrated circular Bragg grating at the semiconductor surface to boost the emission of single photons. For further details see article number 2100002 by Stephan Reitzenstein and co‐workers.